Criminal Acts Performed by Children in the Perspective of Criminology (Case Study in Gorontalo City on 2008-2012) - Sarson, Mohamad Taufiq Zulfikar (Universitas Negeri Semarang, 2020)
This study aims to determine the factors that lead to criminal offenses committed by children in the city of Gorontalo and how the response to the occurrence of criminal offenses committed by children in the city of Gorontalo. Data were collected through interviews, questionnaires. Analysis of the data used is data analysis that seeks to provide a clear and concrete description of the object that are discussed qualitatively and then the data is presented in descriptive technique that uses a frequency distribution test with the formula P = F / N x 100%. The results showed that the root causes of criminal offenses committed by children in the city of Gorontalo is the environmental factor family and social environment, socio-economic condition factor, factor the low level of education, liquor as psychological factors, and factors that are less religious knowledge. Efforts to control criminal offenses committed by children in the city of Gorontalo there are three forms: preventive countermeasures (prevention), attempts repressive and rehabilitation efforts